Child alcohol use in rural kebeles of Amhara region: prevalence, age of onset and association with health and behavior problems - Tiruwork Tola; Meskerem Debele; Melkam Ayalew; Habtamnesh Abegaz; Bizu Zekiros (College of education, Bahir Dar University, 2023)
This study examined the prevalence of child alcohol use, age of onset and association with health and behavior problems in three rural kebeles of Amhara region, Ethiopia. A total of 390 children and 390 mothers were enrolled in the study from Awzet, Yetnora and Zindib Kebeles using cluster sampling techniques. The data were collected through questionnaires. The finding revealed that approximately 82 % of the sample children drink alcohol, and about 50% of them began alcohol use between the ages of 6 months and 12 years. The regression analysis also revealed that statistically significant causal association between children's report of alcohol use and their health and behavior problems and on the reverse statistically non-significant causal association between children's report alcohol use and mothers' report of their children's destructive and aggressive behavior. Finally, it is concluded that majority of children live in this area experiment alcohol at early age which may place them at risk of developing various health and behavior problems.